Numerical Simulation of failure of adhesively bonded composite parts using the cohesive zone method - Horst Knoop (2016)
The present work aims in the proper simulation of failure of adhesive composite joints. In this regard, the simulations are executed using the cohesive zone method implemented in the FEM-solver Nastran at the site of Airbus Defence & Space in Manching. In the context of a validation pyramid, structures of different complexity are nonlinearly analyzed and afterwards compared with the behavior of tested specimen. In the process, the suitability of the method for the engineering sector is studied by evaluating amongst others the required computing costs and the quality of analysis.